Oligometastases in AJCC stage IVc nasopharyngeal carcinoma: A subset with better overall survival. Issue 8 (24th May 2016) - Tian, Yun‐hong; Zou, Wen‐hui; Xiao, Wei‐wei; Zeng, Lei; Yuan, Xia; Bai, Li; Lu, Taixiang; Tian, Yunming; Han, Fei
Abstract: Background: The purpose of this study was to analyze the patterns of metastasis and therapeutic approaches in American Joint Committee on Cancer (AJCC) stage IVc nasopharyngeal carcinoma (NPC). Methods: A retrospective analysis of 263 patients with stage IVc NPC revealed the incidence of bone, liver, and lung metastases was 67.7%, 32.3%, and 16.0%, respectively. All patients received chemotherapy; 160 patients received radiotherapy (RT) to the primary tumor. Results: The factors associated with poor overall survival (OS) were Karnofsky Performance Scale (KPS) ≤70, liver metastasis, multiple‐organ metastasis, ≥6 lesions, no RT to the primary tumor, and <4 chemotherapy cycles. Two subgroups of M1 disease were divided into: M1a (oligometastases) = single‐organ metastases or 1 to 5 lesions; and M1b = multiple‐organ metastases or ≥6 lesions. The 5‐year OS rates for M1a and M1b were 38.7% versus 7.0%, respectively. Conclusion: Patients with oligometastases have significantly better OS than patients with widespread metastases. Long‐term disease‐free survival can be achieved in selected patients with oligometastases after systemic chemotherapy and definitive RT. © 2016 Wiley Periodicals, Inc. Head Neck 38:1152–1157, 2016